Characteristics Study of Parking Land of Kuok Public Health Center - Hasadiqi, Hasbi; Setiawan, Beny; Azriadi, Emon (Journal of Engineering Science and Technology Management, 2026)
This study aims to determine the characteristics and parking space requirements at the Puskesmas Kuok, located in Kuok District, Kampar Regency. Puskesmas Kuok serves as the main healthcare facility in the area and has experienced a steady increase in visitors each year, making the need for adequate parking facilities increasingly important. The research method used was a field survey, with primary data collected through direct observation of the number of vehicles entering and exiting, parking duration, and vehicle types. Secondary data were obtained from the health center, including information on the number of employees, visitors, and the layout of the parking area. The analysis results showed that the highest parking volume occurred on Monday, with 80 motorcycles and 15 cars. The average parking duration was 2.15 hours for motorcycles and 5.12 hours for cars. The highest parking index reached 90% for motorcycles and 93% for cars, indicating that the parking capacity was frequently exceeded, especially during peak hours. This condition caused disorganized parking and reduced visitor comfort. Based on the research findings, it is recommended that the health center reorganize the parking area by providing marked Standard Parking Spaces and consider expanding the parking area to improve efficiency and user convenience.